Advantages of Information Technology in Engineering Education (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article highlights issues related to the emergence of new technologies and software in higher educational institutions, the expansion of computer capabilities, the transition to the category of anachronism of its understanding as a computing tool, which led to the replacement of the term "computer technology" by the concept of "information technology".